2020
DOI: 10.1155/2020/2958623
|View full text |Cite
|
Sign up to set email alerts
|

Wild Edible Plant Nutritional Contribution and Consumer Perception in Ethiopia

Abstract: The scarcity, high cost, and unreliable supply of healthy food in developing countries have resulted in the search for cheap and alternative sources of healthy and nutritious food. Wild edible plants (WEPs) are one of the alternative sources of healthy and nutritious food, and they are crucially important in supporting the global food basket in all parts of the world in general and in sub-Saharan Africa in particular. These wild edible plants have played a significant role in supplying food and nutritional req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 59 publications
2
57
0
Order By: Relevance
“…Presently, malnutrition is a major health problem in Africa, for example, the number of nutrition stunted children increased from 50.4 to 58.5 million between the year 2000 to 2016 [ 3 , 4 ]. According to Duguma [ 5 ], the use of wild indigenous fruits could combat malnutrition and improve food security. Most foods from the wild play an important part in supplying nutrition to communities during periods of food scarcity as they can be consumed as snacks in emergency demands.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, malnutrition is a major health problem in Africa, for example, the number of nutrition stunted children increased from 50.4 to 58.5 million between the year 2000 to 2016 [ 3 , 4 ]. According to Duguma [ 5 ], the use of wild indigenous fruits could combat malnutrition and improve food security. Most foods from the wild play an important part in supplying nutrition to communities during periods of food scarcity as they can be consumed as snacks in emergency demands.…”
Section: Introductionmentioning
confidence: 99%
“…However, food-secure households also regularly enjoy wild edible fruits and plants at some time of the year. It could be surprising that the only sources of nutrition in remote rural communities are wild edible fruits where the domestic fruits are absent in their farming systems and the local markets [6,17].…”
Section: Wild-edible Fruit Species Utilization In Ethiopiamentioning
confidence: 99%
“…Wild edible species can therefore contribute significantly to improved nutrition, income generation, and ecological sustainability [4,5]. ere is an increasing focus on exploring opportunities to tap the potential of valuable underutilized wild plant species for food and nutritional security in the global context [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chenchu tribes collect forest plant foods and products including green leafy vegetables (GLV), roots, tubers, fruits, mahua flowers, honey gum and many indigenous foods including tamarind and sell it to traders and government cooperatives for marginal income. Many studies revealed that indigenous plant foods have been cited as a potential source of essential micronutrients than conventional foods [13]. Epidemiological studies divulge that increased intake of GLV and vegetables are associated with decreased risk towards certain non-communicable diseases particularly cancers, cardiovascular disease, cataract, macular degeneration and other age-related ailments [14].…”
Section: Introductionmentioning
confidence: 99%